In Situ Metabolomics of the Honeybee Brain: The Metabolism of l -Arginine through the Polyamine Pathway in the Proboscis Extension Response (PER) - Pratavieira, Marcel [UNESP]; Da Silva Menegasso, Anally Ribeiro [UNESP]; Roat, Thaisa [UNESP]; Malaspina, Osmar [UNESP]; Palma, Mario Sergio [UNESP] (American Chemical Society (ACS), 2020)
The proboscis extension response (PER) reflex may be used to condition the pairing of an odor with sucrose, which is applied to the antennae, in experiments to induce learning, where the odor represents a conditioned stimulus, while sucrose represents an unconditioned stimulus. A series of studies have been conducted on honeybees, relating learning and memory acquisition/retrieval using the PER as a strategy for accessing their ability to exhibit an unconditioned stimulus; however, the major metabolic processes involved in the PER are not well known. Thus, the aim of this investigation is profiling the metabolome of the honeybee brain involved in the PER. In this study, a semiquantitative approach of matrix-assisted laser desorption ionization (MALDI) mass spectral imaging (MSI) was used to profile the most abundant metabolites of the honeybee brain that support the PER. It was reported that execution of the PER requires the metabolic transformations of arginine, ornithine, and lysine as substrates for the production of putrescine, cadaverine, spermine, spermidine, 1,3-diaminopropane, and γ-aminobutyric acid (GABA). Considering the global metabolome of the brain of honeybee workers, the PER requires the consumption of large amounts of cadaverine and 1,3-diaminopropane, in parallel with the biosynthesis of high amounts of spermine, spermidine, and ornithine. To exhibit the PER, the brain of honeybee workers processes the conversion of l-arginine and l-lysine through the polyamine pathway, with different regional metabolomic profiles at the individual neuropil level. The outcomes of this study using this metabolic route as a reference are indicating that the antennal lobes and the calices (medial and lateral) were the most active brain regions for supporting the PER.
Keywords: honeybee brain; mass spectrometry imaging; memory acquisition; metabolome; neuropils; reflex behavior